Modification of silicophosphate glass composition, structure, and properties via crucible material and melting conditions. (21st October 2019) - Sawangboon, Nuttawan; Nizamutdinova, Alina; Uesbeck, Tobias; Limbach, René; Meechoowas, Ekarat; Tapasa, Kanit; Möncke, Doris; Wondraczek, Lothar; Kamitsos, Efstratios I.; van Wüllen, Leo; Brauer, Delia S.
Abstract: Ceramic crucibles are known to corrode in contact with glass melts. Here, we investigate the effect of alumina and fused silica crucibles on the composition, structure, and properties of silicophosphate glasses. Glasses in the system 0.3 Na2 O‐0.6 P2 O5 ‐0.1 SiO2 were melted in platinum, alumina, or fused silica crucibles at 900°C or 1200°C for 0.5‐12 hours. Al2 O3 and SiO2 were found to leach from the crucibles into the glass melt and alter the glass composition: Al2 O3 content increased with melting temperature and time, resulting in up to 10 mol% Al2 O3 ; SiO2 from fused silica crucibles was also introduced into the glass, resulting in a 25% higher SiO2 content compared to the nominal composition. Glass density, transition temperature, thermal expansion, and mechanical properties were strongly affected by these compositional changes. Based on vibrational spectroscopy, this is explained by increasing numbers of P–O–Al or P–O–Si bonds, resulting in a depolymerization of the phosphate network, and ionic cross‐linking by high field strength aluminum or silicon ions. With increasing alumina content, P–O–Si bonds were replaced by P–O–Al bonds. 31 P and 27 Al MAS NMR spectra revealed that aluminum is present in sixfold coordination exclusively and fully bonded to phosphate species, connecting phosphate groups by P–O–Al–O–P bonds. Abstract : During melting, Al2 O3 leached from an alumina crucible into a silicophosphate melt caused depolymerization of the phosphate network, replacing P–O–P bonds by P–O–Al bonds. Silicon, which was present in sixfold coordination exclusively in the starting glass, was replaced by aluminum, creating some fourfold‐coordinated silicon. Aluminum was present in sixfold coordination exclusively. These structural changes significantly affected glass density, thermal, and elastic properties.